Determination of ethyl carbamate in wine by matrix modification-assisted headspace single-drop microextraction and gas chromatography–mass spectrometry technique - Ma, Zexin; Zhao, Tingyong; Cui, Shiyao; Zhao, Xiaoning; Fan, Yong; Song, Jiangping (Food chemistry, 2022)
•A novel method for the determination of ethyl carbamate in wine has been established.•The application of matrix modification in single-drop microextraction is proposed.•Optimized the formulation of matrix modifiers.•Overcome the negative effect of water on the extraction of ethyl carbamate. A novel method for the analysis of ethyl carbamate in wine has been developed by coupling matrix modification-assisted headspace single-drop microextraction and gas chromatography-mass spectrometry (GC–MS) techniques. The method was developed by optimizing the matrix modifier and extraction parameters. The calibration method was followed by quantifying the internal isotope standard. The results suggested that the method was linear in the concentration range of 2–1000 ng/mL (R2 = 0.9996). The method presents a detection limit of 1.5 ng/mL, and the quantification limit is 5 ng/mL. The accuracy ranged between 94.9 and 99.9%, and the precision of the method was less than 5%. The method was applied for the detection of wine samples, and the results exhibited no significant difference when compared to the solid phase extraction method.